The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/cne.903560210
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine immunoreactivity in the fruit fly Drosophila melanogaster

Abstract: Octopamine has been proposed as a neurotransmitter/modulator/hormone serving a variety of physiological functions in invertebrates. We have initiated a study of octopamine in the fruit fly Drosophila melanogaster, which provides an excellent system for genetic and molecular analysis of neuroactive molecules. As a first step, the distribution of octopamine immunoreactivity was studied by means of an octopamine-specific antiserum. We focused on the central nervous system (CNS) and on the innervation of the larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
170
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 59 publications
12
170
3
Order By: Relevance
“…The presence of exuberant ectopic synapses could reflect efforts by neurons to compensate for the loss of synapses to enhance glutamatergic synaptic transmission. However, we do not favor the idea that formation of ectopic synapses is a result of developmental compensation because 1) ectopic type I boutons are not always found in dennervated muscles; and 2) octopamine, which is the major neurotransmitter in type II synapses (Monastirioti et al, 1995), inhibits glutamate-mediated synaptic potentials instead of enhancing them (Nishikawa and Kidokoro, 1999). Alternatively, these ectopic synapses might result from a defect in either synaptic targeting or nerve sprouting.…”
Section: Flamingo Is Crucial For Both Target Selection and Synaptogenmentioning
confidence: 63%
“…The presence of exuberant ectopic synapses could reflect efforts by neurons to compensate for the loss of synapses to enhance glutamatergic synaptic transmission. However, we do not favor the idea that formation of ectopic synapses is a result of developmental compensation because 1) ectopic type I boutons are not always found in dennervated muscles; and 2) octopamine, which is the major neurotransmitter in type II synapses (Monastirioti et al, 1995), inhibits glutamate-mediated synaptic potentials instead of enhancing them (Nishikawa and Kidokoro, 1999). Alternatively, these ectopic synapses might result from a defect in either synaptic targeting or nerve sprouting.…”
Section: Flamingo Is Crucial For Both Target Selection and Synaptogenmentioning
confidence: 63%
“…Like DLG, GTX was enriched postsynaptically at glutamatergic type I boutons ( Fig. 1G-J ) but absent from type II [octopamine-containing (Monastirioti et al, 1995)] and type III [peptide-containing in muscle 12 ] boutons (data not shown). Like DLG, GTX immunoreactivity was enriched at type Ib boutons, less prominent at type Is boutons (data not shown), and decreased at sites of bouton budding arrow).…”
Section: Dlg Is Required For Proper Synaptic Localization Of Gtxmentioning
confidence: 99%
“…Octopamine, the homolog of norepinephrine in Drosophila, controls many behaviors by activating central G protein-coupled receptors that induce adenylyl cyclase activation and intracellular Ca 2+ release (4,5). Octopamine is also in NMJ boutons at muscles 12 and 13 and can have complex effects at adjacent muscle 6 and 7 NMJs: octopamine inhibits phasic transmission and facilitates tonic release induced by K + , with the latter effect requiring cAMP-dependent protein kinase (PKA) (6)(7)(8). Drosophila motoneurons also contain neuropeptides, which are released in response to nerve stimulation, depolarization, and developmental cues (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%